Is there a link between inflammation and fatigue in multiple sclerosis? - Chalah MA (Dove Medical Press, 2018)
Moussa A Chalah,1,2 Samar S Ayache1–3 1EA 4391, Excitabilité Nerveuse et Thérapeutique, Université Paris-Est-Créteil, Créteil, France; 2Service de Physiologie – Explorations Fonctionnelles, Hôpital Henri Mondor, Assistance Publique – Hôpitaux de Paris, Créteil, France; 3Neurology Division, Lebanese American University Medical Center, Rizk Hospital, Beirut, Lebanon Purpose: Among autoimmune diseases of the central nervous system stands multiple sclerosis (MS), which is characterized by demyelination, synaptopathy, and neurodegeneration. MS fatigue can affect up to 90% of patients and be very disabling, with a drastic impact on their quality of life. To date, the evaluation of MS fatigue has relied mainly on subjective scales, and actual therapeutic interventions are challenged by modest efficacy and numerous undesirable effects. Therefore, finding biomarkers of MS fatigue might help in optimizing evaluation and treatment strategies. The main objective here was to assess the relationship between MS fatigue and inflammatory or other immunomediated markers. Methods: Research was conducted according to PRISMA guidelines. Computerized databases (ie, PubMed/Medline and Scopus) were consulted till February 2018 aiming to identify articles that addressed inflammation and MS fatigue. Studies in English and French published at any time were considered. Results: A total of 27 studies matched the research criteria. Inconsistency existed regarding the relationship between fatigue and the orexin A system, hypothalamus–pituitary–adrenal axis, and cerebrospinal fluid inflammatory markers. As for peripheral markers, although there was scarcity in the available data, serum proinflammatory cytokines (ie, IL6, TNFα, and IFNγ) seem to be associated with MS fatigue. Finally, no link was found between MS fatigue and T-cell populations (ie, CD3+CD4+ T lymphocytes, regulatory T cells) or other peripheral markers of inflammation (ie, CRP, erythrocyte-sedimentation rate, soluble ICAM1). Conclusion: Future large-scale studies would benefit from comparing the relationship between fatigue and immune measures in patients with different disease phenotypes with and without disease-modifying drugs. With the subjective nature of fatigue scales, finding objective biomarkers for fatigue would be of great help. Keywords: pathophysiology, cytokines, interleukins, cerebrospinal fluids, inflammatory markers